1991
DOI: 10.1093/eurheartj/12.suppl_d.26
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoid heart disease--results of follow-up investigations

Abstract: 52 patients thought to have sarcoid heart involvement have been followed up. By administration of a standardized glucocorticoid therapy we demonstrated improvement of patients' symptoms, ECG disturbances, thallium scan defects of left heart muscle and there was 60-70% regression of pulmonary sarcoidosis. There was a low death rate. We conclude that our diagnostic measures are reliable, and that glucocorticoid therapy is efficacious in the early stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…[284][285][286][287]. However, the Stanford group reported that in three cases in which cardiac transplantation was performed, the prognosis was favorable [284].…”
Section: Cardiac Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…[284][285][286][287]. However, the Stanford group reported that in three cases in which cardiac transplantation was performed, the prognosis was favorable [284].…”
Section: Cardiac Transplantationmentioning
confidence: 99%
“…The prognosis of patients with cardiac sarcoidosis seems to be improving, to some extent, due to the use of various types of new agents, such as antiarrhythmic drugs, and the use of pacemaking and defibrillation devices; however, the prognosis has not been clearly shown to improve on an overall basis, especially in cases with cardiac dysfunction (Table 2) [272][273][274][275][276][277][278][279][280][281][282][283][284][285][286][287][288]. here are no reports as yet on the use of betaadrenergic blockers.…”
Section: Cause Of Death and Prognosismentioning
confidence: 99%
“…When ejection fraction is lower than 35%, certain authors recommend as first line a cardioverter defibrillator [168]. When facing a ''normal'' ejection fraction, conduction and rhythm disturbances correspond to a better prognosis [29,35,46,60,97,116,171] with a regression obtained in 92% of cases [8].…”
Section: Stratification Of Riskmentioning
confidence: 99%
“…Finally, heart transplantation can be performed. Indications are the same as all other cardiomyopathies [35,48,59,159,166,171,180,181,[185][186][187][188]. CS diagnostic is frequently done during the histologic examination of the heart [167].…”
Section: Cardiologic Treatmentmentioning
confidence: 99%
“…So zeigten die Nachuntersuchungen in Bad Berka, dass in einem Drittel der Fäl-le die Herzsarkoidose erst dann klinisch auffällig wurde, nachdem die Lungensarkoidose sich radiologisch normalisiert hatte [21]. Daher sollte auch bei jungen Patienten mit unklaren Herzrhythmusstörungen oder Myokardveränderungen differenzialdiagnostisch an eine Sarkoidose gedacht werden.…”
Section: Epidemiologieunclassified